2016
DOI: 10.3855/jidc.7906
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of infectious diseases in São Miguel Island (Azores, Portugal): A hospital-based descriptive study

Abstract: Introduction: We performed a descriptive analysis of molecular diagnosis of infectious agents in the São Miguel Island population, in order to address questions like what is the frequency of clinical requests, is it observable seasonality of pathogens, and what is the positive rate for the clinical diagnosis. Methodology: This was a retrospective and descriptive study based on 878 individuals suspected of harboring infectious diseases during two consecutive years, 2012-2013. More than 25 different pathogens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Many outbreaks of leptospirosis occur in urban slums where some of the world's most deprived and vulnerable people live, where socioeconomic resilience is invariably poor, where access to health care is usually already inadequate and where public health services are often limited [3,25,34]. It has been shown that people who are engaged in agriculture and animal husbandry have higher risk of leptospirosis in comparison to other occupations [16,18,22,23,35,36]. Maybe climate changes that are occurring around the world and in our country as well, explain the increased number of suspicious [37].…”
Section: Discussionmentioning
confidence: 99%
“…Many outbreaks of leptospirosis occur in urban slums where some of the world's most deprived and vulnerable people live, where socioeconomic resilience is invariably poor, where access to health care is usually already inadequate and where public health services are often limited [3,25,34]. It has been shown that people who are engaged in agriculture and animal husbandry have higher risk of leptospirosis in comparison to other occupations [16,18,22,23,35,36]. Maybe climate changes that are occurring around the world and in our country as well, explain the increased number of suspicious [37].…”
Section: Discussionmentioning
confidence: 99%